ICT 4D in the form of e-learning and m-learning - Balwant Singh, Ninderpal Singh; Ahmad, Abdul Mua'ti @ Zamri (IRPN Press, 2014)
This paper provides a critical review on e-learning and m-learning based on studies conducted by two different scholars. The first journal which is written by Matti Hverila and Reza Barkhi, titled “The Influence of Experience, Ability and Interest on e-learning Effectiveness”. The researchers examined the effectiveness of e-learning process based on four areas; learning preconception, prior e-learning experience ability and interest of students. The second journal titled “Mobile learning: From Single Project Status to the Mainstream”, written by Olaf Zawacki-Richter, Tom Brown and Rhena Delport. The researchers try to find out the use of m-learning among distance education practitioners or users. They looked to see if m-learning has caused a paradigm shift and litheness in the area of distance education. The purpose of this paper is also to criticize the methodology used and suggesting dependable method for future research.